DESIGN OF AN ANAEROBIC DIGESTER FOR BIOGAS PRODUCTION FROM COW MANURE BASED ON THE INTERNET OF THINGS (IOT) - Taufiq, Muhammad; Satriananda, S (Jurnal Sains dan Teknologi Reaksi, 2025)
The continuously increasing energy demand drives the utilization of renewable energy, one of which is biogas from cow dung. Biogas production is generally not optimal because fermentation is conducted at room temperature, which is less suitable for methanogenic bacteria. This research designs an Internet of Things (IoT) based anaerobic digester that can monitor and control temperature in real time, while also examining the effect of fermentation temperature on biogas volume and Chemical Oxygen Demand (COD). The temperature of 25°C produced the lowest volume (0.3 L) and COD (9600 mg/L). The optimal fermentation condition is found at a temperature of 35°C. The research results indicate that temperature significantly affects the fermentation process. A temperature of 35°C yields the highest biogas volume (3.7 L) and the lowest COD (6400 mg/L), whereas a temperature of 27°C results in the lowest volume (0.3 L) and COD (9600 mg/L). The optimal fermentation condition is at a temperature of 35°C. The application of IoT facilitates the monitoring of the process and enhances the efficiency of biogas production.Keywords: Biogas, Anaerobic Digester, Internet of Things (IoT), Chemical Oxygen Demand (COD)